Percutaneous sacroplasty. (15th October 2011) - Gupta, Amar C; Yoo, Albert J; Stone, Jeffrey; Barr, John C; Brook, Allan; Tutton, Sean; Ortiz, Orlando; Hirsch, Ariel E; Larvie, Mykol; Frey, Michael E; Jayaraman, Mahesh V; Hirsch, Joshua A
Abstract : The recognition of sacral insufficiency fractures continues to be poor, and diagnosis is often delayed resulting in significant morbidity. Percutaneous sacroplasty is an image guided procedure that is safe and potentially effective for treating the pain and disability related to these fractures. Several cohort studies reviewed here report successful outcomes using this procedure, with patients experiencing nearly full pain relief immediately and longitudinally. As with the well proven results from percutaneous vertebral augmentation within the thoracic and lumbar spine, sacroplasty reduces the cost associated with bed rest and physical therapy and allows patients to return to activities of daily living sooner than with conservative therapy.